Reproduction, denning, and spatial ecology of juvenile, yearling, and adult San Clemente Island foxes (Urocyon littoralis clementae) - Hamblen, Emily Elizabeth, author; Andelt, William F., advisor; Coleman, Robert O., committee member; Stanley, Tom R., committee member; Noon, Barry R., committee member (Colorado State University. Libraries, 2015)
The endemic California Channel Island fox (Urocyon littoralis) declined substantially on four of the six islands that it occupies between 1994 and 2002. One subspecies, the San Clemente Island fox (SCLI; Urocyon littoralis clementae) has maintained a relatively stable population compared to the subspecies that declined. The San Clemente Island fox is listed as threatened by the state of California, thus, increased information on reproductive behavior and success as well as home range area and dispersal is essential for understanding the population dynamics of this species. I used a spatially balanced random sampling design to capture and radio-collar 30 foxes from 31 December 2008 to 10 January 2009. I then captured juvenile island foxes from 20 June to 8 October 2009. I determined reproductive status of 28 island foxes through observations of collared yearlings and adults with or without juveniles between 25 February and fall 2009. A greater proportion of adults (11/20) than yearlings (1/8), and a greater proportion of females (9/12) than males (3/16) were observed interacting with juveniles. Litter sizes averaged 2.0 juveniles. Only one of 28 collared foxes exhibited either polygamous or "helper" behaviors. Parturition started approximately two months earlier than historically recorded on other islands. I observed four dens located in shrubs and one den in a hole without surrounding vegetation. The average slope of terrain next to dens was 6o, average aspect was 148o, and orientation of the most worn entrance to the den averaged 152o. If monetary resources are limited, I suggest focusing on females to monitor and estimate reproductive success because males were infrequently found with juveniles. If emergence from dens continues to occur earlier than previously recorded, then the current recommended time period for trapping (20 June–January) may need to exclude January to reduce stress during pregnancy of females. Our results should help inform future population modeling for the San Clemente Island fox population. Home range sizes varied by age class, whereas sex and type of telemetry (vehicle vs walk-in) did not affect home range size. I did not observe overlap often enough to evaluate differences by age classes, but the largest percentage of overlap occurred between an adult male and yearling male (57.8%) and an adult male with an adult female (47.4%). Five of 17 juveniles, one of nine yearlings, and 0 of 21 adults dispersed. I documented the largest average (3.49 km) and maximum dispersal (10.0 km) of any Channel Island fox study. The presence of dispersal in SCLI foxes suggests that 1) juveniles, and particularly males, should be targeted for vaccination because they are more likely to disperse and possibly transmit diseases than older age classes, and 2) if populations are reduced, island foxes may be able to repopulate areas through dispersal.